The Development of Canva-Assisted Scientific Approach Pythagoras Teaching Materials to Improve Students’ Mathematical Reasoning Ability on Junior High School - Pratiwi, Prisca Mulya; Rohaeti, Euis Eti; Purwasih, Ratni (IKIP Siliwangi, 2024)
This research was conducted to determine the development, feasibility, effectiveness, and difficulties in the development of teaching materials on the Pythagorean Theorem using a scientific approach assisted by Canva to enhance the mathematical reasoning abilities of junior high school students. This research was conducted at SMP PGRI 10 Bandung using the Research and Development (R&D) method based on the 4D stages. The research subjects included 33 students from class IX F for limited trials, 27 students from class VIII B, and 29 students from class VIII D for extensive trials. The research instruments used in this study included interviews in the preliminary learning, student responses to the teaching materials, expert validation sheets, and 6 items of reasoning ability test questions. The material used in this research was the Pythagorean Theorem. Student reasoning ability test data were analyzed using Microsoft Excel calculations. The research results indicate that: 1) the development process of the 4D method teaching materials, including a) Define (Definition); b) Design; c) Develop; and Disseminate, have been successfully implemented according to the plan; 2) the validator calculation results obtained a percentage of 86.21%, categorized as